Kapitał ludzki najistotniejszym elementem w organizacji: Human capital the most important element in the organization - Ciekanowski, Zbigniew (Management and Administration Journal, 2021)
In the elaboration „Human capital the most important element in the organization‟ first was presented the development of human resources in the course of a few centuries. Then it was showed how important human resources are for an organization and how significant is the selection of the crew as it is not only the base for proper fulfilling tasks but also serves as a peculiar stimulant to its development. A person by introducing his skills and specialized knowledge gets involved in the important company matters. It was also stressed how important thing is to invest into human resources and to keep trained staff within the company. These are a key element of the employment process. An employer by taking care of his employees indirectly is taking care of his company. At the end all conclusions were introduced which unambiguously show that human resources constitute the company‟s most important factor. The knowledge and skills is synonymous to financial results of a company. Investments into human resources open great perspectives and their lack hamper its development.